The Relationship Between Plasma Selenium, Antioxidant Status, Inflammatory Responses and Ischemic Cardiomyopathy: A Case-Control Study Based on Matched Propensity Scores - Luo Y; He X; Hu L; Zhao J; Su K; Lei Y; Li Y (Dove Medical Press, 2022)
Yinhua Luo,1,* Xiaohong He,2,* Linbo Hu,3 Jinbo Zhao,1 Ke Su,1 Yuhua Lei,1 Yuanhong Li1 1Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Shiyan, People's Republic of China; 2Centre for Disease Control and Prevention, Enshi Center for Disease Control and Prevention, Enshi Prefecture, People's Republic of China; 3Health Management Centre, Central Hospital of Tujia and Miao Autonomous Prefecture, Enshi Prefecture, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuanhong Li, Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Shiyan, People's Republic of China, Email lyh0101@vip.163.comBackground: Ischemic cardiomyopathy (ICM) with high morbidity and mortality is closely associated with an abnormal equilibrium of circulation selenium levels. The oxidative stress theory is the most accepted theory of selenium causing ischemic cardiomyopathy. However, the role of inflammatory responses in ICM has received limited attention.Methods: This study included 119 subjects, 43 of whom were patients with ICM, and 76 were healthy controls. Blood specimens were collected from subjects and serum levels of inflammatory and oxidative stress indicators and plasma levels of selenium were measured.Results: When plasma selenium and indicators of inflammation and oxidative stress were compared between groups, plasma selenium levels were significantly lower in the ICM group than in the control group (68.83874 vs 104.39775, p=0.02032), while indicators of inflammation such as tumour necrosis factor-alpha (TNF-α) (79.09773 vs 46.15634, p< 0.001), interleukin-6 (IL-6) (49.41484 vs 38.46923, p< 0.01) and neutrophil/lymphocyte ratio (3.696574 vs 2.383658, p< 0.001) were significantly higher in the ICM group than in the control group (all of these results were statistically different). Additionally, malondialdehyde (MDA), a marker of oxidative stress, was considerably higher in the ICM group than in the control group (61.63078 vs 39.0609, p< 0.01). In contrast, there were no significant differences in superoxide dismutase (SOD) levels between groups (p> 0.05). The Poisson regression analysis revealed a significant association between selenium and high levels of MDA, IL-6 and TNF-α (p< 0.05). Additionally, selenium was negatively connected with SOD levels and the neutrophil/lymphocyte ratio, but this relationship was not statistically significant (p=0.96, 0.15, respectively).Conclusion: Selenium deficiency is strongly associated with the development of ICM, and with levels of inflammation and oxidative stress in patients with ICM. Selenium can prevent the development and delay the progression of ICM by alleviating inflammatory responses.Keywords: inflammatory responses, ischemic cardiomyopathy, oxidative stress, selenium